Application and prospect of near infrared imaging and spectroscopy analysis on quality inspecting of agricultural products - XU Hui-rong; YING Yi-bin (浙江大学学报. 农业与生命科学版)
In this paper the recent applications and development of NIR imaging and NIR spectroscopy analysis on quality inspecting of agricultural products in overseas were introduced. It was concluded that NIR imaging and NIR spectroanalysis would be very useful in the nondestructive external and internal quality inspecting of agricultural products.